Development a mitigation strategy of enniatins in pasta under home-cooking conditions. (January 2016) - Serrano, A.B.; Font, G.; Mañes, J.; Ferrer, E.
Abstract: The effect of pasta cooking on the enniatins (ENs) contents was evaluated in white and whole-grain pasta. The cooking of pasta was performed for 10 min in boiling water. ENs were extracted from raw and cooked pasta by Solid-Liquid extraction with acetonitrile, and from cooking water by Dispersive Liquid–Liquid Micro-Extraction (DLLME) with a mixture of acetonitrile and carbone tetrachloride. Mycotoxin analysis was performed by Liquid Chromatography coupled to Tandem Mass Spectrometry. The effect of pasta cooking has a marked influence on the reduction of ENs levels. Reductions of 98–100% for ENA, 94–95% for ENA1, 14–49% for ENB and 53–65% for ENB1 were achieved after the process. ENs were detected at low concentration levels in water samples. Moreover, it was developed a mitigation strategy to reduce the ENs contents by the combining effect of the thermal treatment and the pH during cooking pasta. The modification of the pH in the cooking water to pH 4 resulted in percentages of reduction close to 100%, while the modification to pH 9 provided percentages from 44 to 100%. Two degradation products were tentatively elucidated after the thermal treatment by Liquid Chromatography-Quadrupole-Linear Ion Trap-Mass Spectrometry. Highlights: Cooking of pasta resulted in reductions of 94–100% for ENs type A. ENs type B were relatively stable to cooking of pasta with reductions of 14–65%. Percentages of reduction were of 100% after pasta cooking at acid pH. Two new compounds were tentatively elucidated in cooked pasta and cooking water.